Impact of the disclosure of financial instruments in accordance with the requirements of IFRS 7 on the financial performance of banks: Evidence from Bahrain - Alsammarraee, Ammar Esam AbdulRahman; Alalkawi, Talal; Alshareeda, Nadya AbdulJabbar (Journal of Economic, Administrative and Legal Sciences, 2019)
A key objective of the research is to determine the extent to which conventional Bahraini banks- the retail sector- comply with the requirements for disclosure of financial instruments in accordance with the requirements of IFRS 7, As well as measuring the impact of that compliance on the financial performance of those banks. The descriptive and analytical approach adopted In order to achieve these objectives. A survey questionnaire consisting of 27 paragraphs of IFRS 7 was used to identify the banks that comply with the requirements of that standard, and then to measure the impact of Bahraini banks' compliance with the requirements of the said standard on their financial performance.In order to analyze the data and test the hypotheses, the SPSS program was used. The most important results were: Bahraini conventional banks- retail sector- comply with the requirements of IFRS 7 and there is also an impact of the compliance of the Bahraini conventional banks –retail sector- on financial performance is measured by the rate of return on assets.Finally, the study recommended increasing the awareness of employees in conventional banks in the Kingdom of Bahrain of the importance of applying financial reporting standards including IFRS 7 and their impact on the financial performance of banks.
Keywords: traditional banks; financial performance; International Financial Reporting Standard No. 7